Interleukin-4 Programmed Macrophages Suppress Colitis and Do Not Enhance Infectious-Colitis, Inflammation-Associated Colon Cancer or Airway Hypersensitivity - Callejas, Blanca E.; Blyth, Graham A. D.; Jendzjowsky, Nicholas; Wang, Arthur; Babbar, Anshu; Koro, Konstantin; Wilson, Richard J. A.; Kelly, Margaret M.; Cobo, Eduardo R.; McKay, Derek M. (Frontiers in Immunology, 2021)
The murine interleukin-4 treated macrophage (M(IL-4)) exerts anti-inflammatory and pro-healing effects and has been shown to reduce the severity of chemical-induced colitis. Positing M(IL4) transfer as an anti-inflammatory therapy, the possibility of side-effects must be considered. Consequently, bone marrow-derived M(IL4)s were administered via intraperitoneal injection to mice concomitant with Citrobacter rodentium infection (infections colitis), azoxymethane/dextran sodium sulphate (AOM/DSS) treatment (a model of colorectal cancer (CRC)), or ovalbumin sensitization (airway inflammation). The impact of M(IL4) treatment on C. rodentium infectivity, colon histopathology, tumor number and size and tissue-specific inflammation was examined in these models. The anti-colitic effect of the M(IL4)s was confirmed in the di-nitrobenzene sulphonic acid model of colitis and the lumen-to-blood movement of 4kDa FITC-dextran and bacterial translocation to the spleen and liver was also improved by M(IL4) treatment. Analysis of the other models of disease, that represent comorbidities that can occur in human inflammatory bowel disease (IB), revealed that M(IL4) treatment did not exaggerate the severity of any of the conditions. Rather there was reduction in the size (but not number) of polyps in the colon of AOM/DSS-mice and reduced infectivity and inflammation in C. rodentium-infected mice in M(IL4)-treated mice. Thus, while any new therapy can have unforeseen side effects, our data confirm and extend the anti-colitic capacity of murine M(IL4)s and indicate that systemic delivery of one million M(IL4)s did not exaggerate disease in models of colonic or airways inflammation or colonic tumorigenesis.